Study of Heavy Metals (Pb, Cu, and Zn) in Ark Cockle’s (Anadara inflata) Flesh and Shell in Selat Panjang Waters Kep. Meranti - Pane, Dedi Muksin; Ikhwan, Yusni; ', Elizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Ark cockle (Anadara inflata) is one of bivalve species found in Selat PanjangWaters. It is used as indicator of heavy metals pollution because of filter feedercharacteristic and of sedentary life mode. The objective of this study was to determine theconcentration of lead (Pb), Cuprum (Cu) , and Zincum (Zn) in ark cockle’s flesh and shellin Kronjo and Cituis. Heavy metals Pb, Cu, and Zn were analyzed by Atomic AbsorptionSpectrofotometer (AAS).The result showed that the consentration of Pb (3,81 μg/g) in ark cockle’s shell washigher than that of ark cockle’s flesh in contrary the consentration of Cu and Zn (6,03 μg/gand 7,54 μg/g) in ark cockle’s flesh was higher than concentration of Cu and Zn in arkcockle’s shell. Based on assisment of PWTI (Provisional Tolerable Weekly Intake) for heavymetals (Pb, Cu and Zn) in ark cockle A. inflata in Selat Panjang Waters, Meranti Island thatark cockle A. inflata safe to consumtion.Key words: Heavy Metals, Ark Cockle and Selat Panjang Waters